Relationship between Craniovertebral Abnormalities and Maxillary Lateral Incisors Agenesis: A Case-Control Study - Farhad Sobouti; Mehdi Aryana; Seyed Mohammad Ghadiri; Kiarash Modanloo; Sepideh Dadgar (International Journal of Dentistry)
Objectives. This study aimed to investigate whether the sella turcica bridging (STB) and ponticulus posticous (PP) are associated with the congenital missing maxillary lateral incisor (CMMLI), based on lateral cephalograms of patients who needed orthodontic treatment. Materials and Methods. This case-control study examined 160 panoramic images and lateral cephalograms of 2000 patients seeking orthodontic treatment. The case group included 80 patients with CMMLI (40 with unilateral and 40 with bilateral CMMLI) and the control group included 80 patients without CMMLI. Panoramic images were used to diagnose CMMLI and lateral cephalograms showed STB and PP extension. The researchers used statistical analyses to examine the relationship among STB, PP, and CMMLI (P<0.05). Results. The prevalence of STB type I, II, and III was 47.5%, 35%, and 17.5% in the case group and 72.5%, 22.5%, and 5% in the control group, respectively, determining a positive relationship between CMMLI and STB and a significant relationship between bilateral CMMLI and STB (P<0.05 for both). The prevalence of normal, incomplete, and complete PP extension was 80%, 5%, and 15% in the case group and 82.5%, 5%, and 12.5% in the control group, respectively. There was no significant relationship between CMMLI and PP extension (P>0.05) and between the STB and the PP extension (P>0.05). Conclusion. CMMLI was significantly related to STB but not to PP extension. Investigating the relationship between unilateral/bilateral CMMLI, STB, and PP has shown only a significant relationship between bilateral CMMLI and STB. There was no significant relationship between STB and PP extension.